A pyroptosis‐related signature predicts prognosis and indicates immune microenvironment infiltration in glioma. (26th September 2022) - Chen, Jia; Chen, Shanwei; Li, Bingxian; Zhou, Shaojiong; Lin, Han
Abstract: Background: Glioma, the most common malignant brain tumor, leads to high recurrence rates and disabilities in patients. Pyroptosis is an inflammasomes‐induced programmed cell death in response to infection or chemotherapy. However, the role of pyroptosis in glioma has not yet been elucidated. Methods: RNA‐seq data and clinical information of 660 gliomas and 847 samples were downloaded from the TCGA and CGGA, respectively. Then, data of 104 normal brain tissues was retrieved from the GTEx for differential expression analysis. Twelve pairs of peritumoral tissue and glioma samples were used for validation. Gene alteration status of differentially expressed pyroptosis‐related regulators in gliomas was detected in cBioPortal algorithm. Consensus clustering was employed to classify gliomas based on differentially expressed pyroptosis‐related regulators. Subsequently, a PS‐signature was constructed using LASSO‐congressional analysis for clinical application. The immune infiltration of glioma microenvironment (TME) was explored using ESTIMATE, CIBERSORT, and the other immune signatures. Results: cBioPortal algorithm revealed alteration of these regulators was correlated to better prognosis of gliomas. Then, our study showed that pyroptosis‐related regulators can be used to sort out patients into two clusters with distinct prognostic outcome and immune status. Moreover, a PS‐signature for predicting the prognosis of glioma patients was developed based on the identified subtypes. The high PS‐score group showed more abundant inflammatory cell infiltration and stronger immune response, but with poorer prognosis of gliomas. Conclusion: The findings of this study provide a therapeutic basis for future research on pyroptosis and unravel the relationship between pyroptosis and glioma prognosis. The risk signature can be utilized as a prognostic biomarker for glioma.